Circulating Serum-Derived Microparticles Provide Novel Proteomic Biomarkers of Spontaneous Preterm Birth - Ezrin, Alan M.; Brohman, Brian; Willmot, Jackie; Baxter, Sarah; Moore, Keith; Luther, Mike; Fannon, Michael R.; Sibai, Baha (American Journal of Perinatology, 2015)
Objective The purpose of this study was to determine whether the proteomic biosignature of circulating microparticles in maternal serum obtained in the second trimester could identify pregnancies that result in spontaneous preterm birth (SPTB).Study Design Microparticles were isolated from blinded biorepository-sourced serum samples from 48 pregnant women at 15 to 17 weeks of gestation. Microparticle proteins were extracted and analyzed using label-free liquid chromatography/mass spectrometry. Peptide features were analyzed to assess the association of specific protein patterns with subjects delivering at term (≥ 37 weeks gestation; n = 24) and those experiencing SPTB (≤ 34 weeks gestation; n = 24).Results We found 99 proteins that had statistically significant differences in signal intensity between term and SPTB women in both first (n = 26) and second (n = 22) singleton gestation pregnancy cohorts. Additional evaluation identified 18 biomarkers that met criteria for further priority evaluation (12 preterm, 6 term). Pathway analysis showed that differentiating SPTB biomarker proteins were predominantly associated with inflammation and cell injury, while differentiating term biomarkers were associated with cell growth and hematological parameters.Conclusion This study shows for the first time that the proteomic content of serum microparticles isolated in the second trimester can identify with a high degree of accuracy pregnancies that result in SPTB.
Keywords: preterm birth risk; molecular diagnostic; circulating microparticle; proteomics; microvesicle; exosome